The role of Psycap and Readiness for change of hotel employees in implementing the CHSE protocol - David Kristianto; Endo Wijaya Kartika; Vido Iskandar (Universitas Merdeka Malang, 2022)
To prevent the transmission of the Covid-19 virus, the hotel industry continues to improve, especially with regard to health protocols, therefore the Hotel has started implementing the Cleanliness, Hygiene, Sanitation, and Environment (CHSE) protocol, this protocol was created by the government to increase efforts to prevent and control transmission Covid-19 for the public in public places and facilities to prevent new clusters of transmission. The implementation of the CHSE protocol requires the readiness of all hotel employees to implement it. This research is a causal quantitative research that aims to see the readiness of star hotel employees in Surabaya, Malang, and Batu to implement changes seen from 4 dimensions, namely Self-Efficacy, Optimism, Hope, Resilience. This research was conducted by distributing questionnaires to 68 hotel employees, where the majority of respondents came from the FB Service department 29 people (42.65%) and the Front Office 18 people (26.47%) FB Culinary 11 people (16.18%), Housekeeping 6 people ( 8.82%), Security 4 people (5.88%). Data processing in this study uses the help of smart PLS 2.0. From the results of this study it can be concluded that 4 dimensions, namely Self-Efficacy, Optimism, Hope, Resilience have a positive and significant effect on employee readiness in implementing changes.